2020
DOI: 10.1101/gad.330050.119
|View full text |Cite
|
Sign up to set email alerts
|

Human RTEL1 associates with Poldip3 to facilitate responses to replication stress and R-loop resolution

Abstract: RTEL1 helicase is a component of DNA repair and telomere maintenance machineries. While RTEL1's role in DNA replication is emerging, how RTEL1 preserves genomic stability during replication remains elusive. Here we used a range of proteomic, biochemical, cell, and molecular biology and gene editing approaches to provide further insights into potential role(s) of RTEL1 in DNA replication and genome integrity maintenance. Our results from complementary human cell culture models established that RTEL1 and the Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…This is supported by our observation that overexpression of WT RNaseH1-GFP partially rescues the reduced fork extension rates, fork asymmetry, micronuclei, and 53BP1 and γH2AX foci in Rtel1 −/− ( Figures 3 A–3F) and Rtel1 PIP_box knockin ( Figures 3 I, 3J, and S4 A) cells. This implies that RTEL1 is important for the removal of R-loops in a PIP-box-dependent manner, which is consistent with a recent paper showing that Poldip3 facilitates RTEL1 recruitment to chromatin to remove R-loops ( Björkman et al., 2020 ). We previous established that increased replication fork stalling and/or collapse is the primary source of replication problems in Rtel1 −/− and Rtel1 PIP_box knockin cells ( Vannier et al., 2013 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is supported by our observation that overexpression of WT RNaseH1-GFP partially rescues the reduced fork extension rates, fork asymmetry, micronuclei, and 53BP1 and γH2AX foci in Rtel1 −/− ( Figures 3 A–3F) and Rtel1 PIP_box knockin ( Figures 3 I, 3J, and S4 A) cells. This implies that RTEL1 is important for the removal of R-loops in a PIP-box-dependent manner, which is consistent with a recent paper showing that Poldip3 facilitates RTEL1 recruitment to chromatin to remove R-loops ( Björkman et al., 2020 ). We previous established that increased replication fork stalling and/or collapse is the primary source of replication problems in Rtel1 −/− and Rtel1 PIP_box knockin cells ( Vannier et al., 2013 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the cause of fork stalling and/or collapse was unknown. Our findings and those of others ( Björkman et al., 2020 ; Takedachi et al., 2020 ; Wu et al., 2020 ) suggest that the replication defects in Rtel1 -deficient cells are primarily caused by TRCs resulting from inefficient removal of G4/R-loops. While the precise mechanism by which RTEL1 counteracts G4/R-loops remains to be defined, RTEL1 can unwind telomeric G4s in vitro ( Vannier et al., 2013 ), so it could use this activity to remove G4s within a G4/R-loop.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, the results obtained in C2C12 suggest another possible mechanism on how TDP-43 may control gene expression in muscle in an indirect fashion and eventually participate in disease. Recently, loss of TDP-43 was associated with increased genomic instability and R-loop formation (Giannini et al, 2020;Wood et al, 2020) possibly through mechanisms involving Poldip3, which has been shown to play a role in maintaining genome stability and preventing R-loop accumulation at sites of active replication (Björkman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…RTEL1 unwinds D-loops in vitro, while tethering of RTEL1 to telomeres via a TRF2-S365A mutant reduces t-loop levels in vivo, suggesting RTEL1 unwinds t-loops directly (Barber et al 2008;Vannier et al 2012). However, RTEL1 also unwinds telomeric G-quadruplex structures and possibly RNA-DNA hybrids (R-loops), although RTEL1 is recruited to these secondary structures through an interaction with PCNA, not with TRF2 (Vannier et al 2012;Björkman et al 2020;Wu et al 2020). Therefore, RTEL1 might also impact t-loops indirectly, by unwinding secondary structures that alter topological stress within the telomere.…”
Section: T-loops As Pathological Structuresmentioning
confidence: 99%